Analisis Pemilihan Supplier Bahan Baku Tas Gitar dengan Metode Fuzzy Analytical Hierarchy Process (FAHP) di PT. True Indonesia - Wahyu, Imas Prisma; Pulansari, Farida (Universitas Batanghari Jambi, 2024)
The use of high-quality raw materials will affect the quality of products produced by a company. Companies really need suppliers who can supply quality raw materials. This can be realized by selecting the most appropriate supplier so that the company can minimize problems that can occur regarding raw material suppliers. PT True Indonesia is a manufacturing company that produces music equipment bags. So far, the company has made decisions in choosing suppliers only with the intuition of the parts related to the procurement of these raw materials. The decision chosen by the company in determining this supplier is often not right. The problems experienced by the company are the quality of raw materials that do not meet the company's criteria and the supplier's delay in sending raw material orders. In this study, the Fuzzy Analytical Hierarchy Process (FAHP) method was used. There are 7 main criteria in choosing a polyester fabric supplier, namely quality, delivery, price, communication system, warranties and claim policies, performance history, and geographic location. From the calculations carried out, the best polyester fabric supplier ranking for PT True Indonesia in order, Tongxiang has a total value of 0,3395, Hantron has a total value of 0,3350, PT. Lambang Jaya has a total value of 0,3340, PT. Shinta Indah Jaya has a total value of 0,3174, and CV. Agung has a total value of 0.3116.